Analisis Kesehatan Dan Keselamatan Kerja di PT Safindo Raya - Keyla Harista Nasution; Susilawati Susilawati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Accidents or injuries at work can disrupt the productivity and operational efficiency of PT. Safindo Raya. The research background may include efforts to identify and reduce factors that can cause these disorders, thereby increasing the overall efficiency of the company. One of the main objectives of K3 research is to improve employee safety in the workplace. Research can help in identifying potential risks, analyzing the causes of accidents or incidents, and developing strategies to prevent similar incidents in the future. Companies such as PT. Safindo Raya may have an obligation to comply with K3 regulations and standards set by the government or regulatory bodies. K3 research can help companies ensure that they comply with all applicable regulations and achieve the required safety standards. OSH research can also contribute to increasing productivity and efficiency in the workplace by reducing absenteeism due to work-related injuries or illnesses, reducing production downtime due to accidents, or identifying ways to promote safer and more efficient work processes. With this approach, information is collected through questionnaires or interviews with employees, management or K3 staff. These surveys may include employees' perceptions of OSH conditions in the workplace, their understanding of safety procedures, or specific problems they encounter in carrying out their duties. The majority of employees show a high level of awareness of the importance of K3 in the workplace. They expressed an understanding of the importance of using personal protective equipment (PPE) and existing safety procedures. Interview results indicate that expansion of K3 training may be necessary to make employees aware of each job they have a comprehensive understanding of potential risks in the workplace and the precautions that must be taken.